Hamlet on the 20th-Century Russian Stage - Шамина, Вера (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The essay addresses the history of staging Hamlet in the Soviet and post-Soviet Russia. It is based both on the reviews by influential critics of the past and on the personal impressions of the author herself at the turn of the 21st century. The analysis of the dynamics of staging Hamlet in Russia leads to the conclusion that Shakespeare’s tragedy has always functioned like a seismograph, registering every little change in the society and reflecting the general intellectual ambience and attitudes of the Russian intelligentsia.